Maintenance Therapy of Psychosis Spectrum Disorders in a Real-World Setting: Antipsychotics Prescription Patterns and Long-Term Benzodiazepine Use - Maric, Nadja P.; Andric Petrovic, Sanja; Russo, Manuela; Jerotic, Stefan; Ristic, Ivan; Savić, Bojana; Pemovska, Tamara; Milutinovic, Milos; Ribic, Emina; Markovska-Simoska, Silvana; Dzubur Kulenovic, Alma; Jovanovic, Nikolina (Frontiers in Psychiatry, 2022)
Background: Maintenance therapy of patients with primary psychosis spectrum disorders (PSD) in the Western Balkans has received limited interest so far. The present study aimed to investigate long-term prescription patterns among outpatients with PSD. Methods: Information about prescription of antipsychotics (AP), benzodiazepines (BZD) and other psychotropic medication over a 6-month period was collected from outpatients (n=134; ICD-10 diagnosis F20-29) recruited by a larger multi-site study, to find mean daily number of psychotropic drugs, AP prescription patterns (including AP daily dose, route of administration, monotherapy vs. polypharmacy) and BZD utilisation (long-term add-on BZD therapy). Additionally, sex-differences in the aforementioned variables were explored. Results: Clinically stable outpatients (age 41.7±11.0; male 62.7%) were prescribed 2.8±1.1 psychotropic medications daily. The mean 6-month AP dose was 14.2±7.8 mg olanzapine equivalents. Long acting injectable AP was prescribed to 25.2% of the patients. Long-term AP monotherapy was found in 52.7%patients and the majority of them were prescribed second generation AP (65.2%). Long-term AP polypharmacy (42.7%) was more common in males (p=0.015). The most frequent co-prescription patterns were first generation AP plus clozapine. The highest rate of long-term AP co-prescription was found for BZD (in 42.7% cases, average 6-months daily dose of 2.8±2.7 mg lorazepam equivalents) and anticholinergics (33.6%). Conclusion: Existing appropriately designed interventions aiming to safely switch the inappropriate therapeutic regimens - very high prevalence of long-term AP polypharmacy and non-rational BZD co-prescription, should be implemented in the region of Western Balkans.